A map-matching algorithm based on graphics - Yang Qiangrong; Wang Meiling; Yang Hua (Chinese Control Conference, 2013)
Some existing map-matching algorithms have some defects in the robustness and working in real-time. However, the computational geometry algorithms only use the non-numerical methods which make it easy and fast to get the results. But the existing algorithms based on computational geometry can't work in the situation that the main roads and the side roads are paralleled to each other. To solve the problems mentioned above, a map matching algorithm based on graphics is proposed in this paper. The algorithm proposed in this paper utilizes the method which is used to determine whether the segment is intersected with the polygons in graphics to determine the candidate road set. And in the process of getting the match road, if the current position is not in the only confidence region of the candidate roads, the algorithm gets the match road by checking if the position property (the current position is in which side of the road) has changed for more than 3 times. If so, the road is chosen as the match road. By doing this, the algorithm can choose the candidate road set and match the vehicle to the roads effectively. Through real car tests, the correct matching rate is no less than 95% and the time for single point matching is no more than 0.9 ms.